Tag Counting and Monitoring in Large-Scale RFID Systems Theoretical Foundations and Algorithm Design - Yu, Jihong; Chen, Lin (Springer International Publishing : Imprint: Springer, 2019)
This book provides a comprehensive treatment of the theoretical foundation and algorithmic tools necessary in the design of efficient tag counting and monitoring algorithms in emerging RFID systems. The book delivers an in-depth analysis on the following problems ranging from theoretical modeling and analysis, to practical algorithm design and optimization: Stability analysis of the frame slotted Aloha protocol, the de facto standard in RFID tag counting and identification; Tag population estimation in dynamic RFID systems; Missing tag event detection in the presence of unexpected tags; Missing tag event detection in multi-group multi-region RFID systems. The target readers are researchers and advanced-level engineering students interested in acquiring in-depth knowledge on the topic and on RFID systems and their applications.